BEHAVIOURAL TRAINING IN PARTNER COMMUNICATION AND CORRECT CONDOM USE SKILLS - Robles Montijo, Susana; Moreno Rodríguez, Diana; Frías Arroyo, Beatriz; Rodríguez Cervantes, Martha; Barroso Villegas, Rodolfo; Díaz González, Eugenio; Díaz González, Anaya; Rodríguez Campuzano, María de Lourdes; Hernández Pozo, Rocío (Anales de Psicología / Annals of Psychology, 2006)
This study assessed the effects of sexual communication and condom use skills training on 50 sexually active college students’ consistent condom use. In vivo sexual communication and condom use skills postintervention assessments showed that intervention group participants acquired the skills trained and were significantly better than control group participant in openly talking about sex (p<.01), negotiating condom use (p<.01) and correctly using it (p<.001). The condom use indirect measures showed an increment on intervention group in condom use in the last sexual intercourse and consistent condom use, however, there was no statistical significance between groups in condom use for general sexual relationship (p=.869), the last sexual intercourse they recalled (p=.311), and consistent condom use (p=.082). Neither of the three trained target behavioral skills were correlated with any of the self-report condom use measures. Based on these findings this paper questions the validity of indirect measures of condom use and highlights the need to include behavioural measures and training of correct condom use and its relation to condom negotiation skills as part of any intervention program related to HIV/AIDS prevention.